Hubungan Pengetahuan Ibu Dengan Penanganan Pertama Pada Balita Kejang Demam Di IGD Rsud Pariaman - Yesi Maifita; Miftakhul Zanah (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2023)
Febrile seizures are included in the top 3 diseases that are complained about in toddlers. Febrile seizures are seizure awakenings that occur in a rise in body temperature, temperatures above 38°C. Febrile seizures are emergency conditions that require first treatment. Early treatment of febrile seizures depends largely on parents, especially the mother. So that it can provide help to children and not to aggravate the child's condition. This research was conducted on October 4 – October 20, 2023. This study aims to determine the knowledge of mothers with the first treatment of febrile seizure toddlers in the emergency room of Pariaman Hospital in 2023. This type of research is quantitative with Cross Sectional Study approach. The sampling technique used is Accidental Sampling, which involves as many as 34 respondents. Statistical tests using Chi-Square found that most mothers had a less knowledge level on toddler febrile seizures as many as 15(44,1 %) Respondents, and most mothers did less handling on toddler febrile seizures as many as 14 (41,2 %).Respondents. There is a significant relationship between maternal knowledge and the first treatment of febrile seizures with p value = 0.07 where p value < a = 0.05. Based on this study shows that parental knowledge affects the first treatment of febrile seizures. It is recommended to parents to increase knowledge of febrile seizures well, so that they can do the first treatment of febrile seizures.